Obligations and Irony in the Workplace Accomodations: A Case STudy in a Large Corporate Office - Chin, Peter; Hutchinson, Nancy L.; Versnel, Joan; Munby, Hugh; Stockley, Denise (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2008)
This paper reports a multiple-perspective case study of a worlcer with a severe visual impairment and the accommodations that she received and made in a workplace that was conszdered a leader in hiring and accommodating workers with disabilities. Data for the study consisted of observations in the offices of this large corporation, interviews with the focal individual as well as with her supervisor, a colleague, and a human resources professional. Standard qualitative analyses were guided by six facets of negotiating accommodations derived from an extensive review of literature across a number of disciplines. The six facets are: (a) access and disclosure; (h) structural affordances; (c) social context; (d) motivation; (e) understanding of social policy; and ( f ) cognitive problem solving. By attending to these six facets, we demonstrate the ironies that abound in workplaces that emphasize providing accommodations, primarily structural accommodations, while ignoring the process of negotiating accommodations proactively. Ironies also arise in the use of technology to provide structural accommodations while ignoring the power of technology to educate coworkers and supervisors about social policy and to enable ongoing collaborative and cognitive problem-solving as a way of negotiating accommodations. Perhaps the policy should promote duty to negotiate as well as duty to accommodate. Cet article analyse sous plusieurs angles le cas d’une travailleuse aux prises avec une dificience visuelle grave en rapport avec les am6nagements effecttks, par l’employeur et elkmgme, dans un milieu de travail considiri comme un chef de file en matisre d’embauche et d’ame’nagements pour les travailleurs handicape’s. Les dondes utilise’es dans cette e’tude prouiennent d’observations effectue’es dans les bureaux de cette waste entrepnse, d’entrevues auec h travailleuse concerne’e ainsi qu’avec son superviseur, un colkgue et un professionnel des ressources hurnaines. analyse qualitative standard effectde par l’auteur repose sur six aspects relatifs & h ne’gociation d’am’nagements, e’tablis h la suite d’une minutieuse analyse de la documentation pertinente dans une varie’te’ de disciplines. Ces six aspects sont : a) l’accessibilite’ et la divulgation; b) les ressources structurelles; c) le contexte social; d) la motivation; e) la compre’hension des politiques; et f) la re’solution de probhe cognitive. En nous appuyant sur ces six aspects, nous avons montre’ l’ironie qui rsgne dans certains lieux de travail qui se targuent d’offrir des ame’nagements, principalement d’ordre swucturel, alors qu’ils omettent de ne’gocier des am&nagements de fagon proactive. Cette ironie se manifeste e’galement dans l’utilisation, par les entreprises, de la technologie pour offrir des ame’nagements structurels, alors qu’elles n’ont pas recours h la puissance de cette technologie pour informer les collsgues et superviseurs au sujet des politiques sociales et pour faciliter l’e’tablissement d’un processus coope’ratif et cognitif de re’solution de probkmes visant h ne’gocier des ame’nagements. Les politiques dewaient peut-&me faire la promotion de l’obligation de dgocier paralklement h l’obligation d’effectuer des ame’nagements.